Reading Judas : the Gospel of Judas and the shaping of Christianity - Pagels, Elaine H., 1943-; King, Karen L., 1954- (New York : Penguin Books, 2008)
Evaluates the meaning of the controversial, newly-discovered Gospel of Judas, illustrating how the text offers an understanding of Judas's betrayal, the apostles' understanding of Jesus's death, and God's role in the crucifixion.
Part One: Reading Judas / Elaine Pagels and Karen L. King : Judas: betrayer or favored disciple? -- Judas and the Twelve -- Sacrifice and the life of the spirit -- The mysteries of the kingdom -- A final note -- Part Two: The Gospel of Judas / Karen L. King : English translation of the Gospel of Judas -- Comments on the translation.
Originally published: New York : Viking, 2007.
Includes bibliographical references (pages 169-190) and index.
Keywords: Gospel of Judas -- Criticism, interpretation, etc; Gospel of Judas; Gospel of Judas -- Criticism; Criticism, interpretation, etc